The Urgency of Indonesia to Control Imports of Non-Hazardous and Toxic Waste (B3) in 2019 - Al Dina Maulidya; Melina Nur Fitriah; Eva Yusnita Chandra (Universitas Muhammadiyah Malang, 2019)
This study discusses the urgency of Indonesia to implement the regulation of imports of non-hazardous and toxic waste (B3) in 2019. The background of this research is when there was an urging from Ministry of Environment and Forestry towards the Ministry of Trade to revise regulations related to the import of non-B3 waste in 2019. Other than that, the revision of the regulation on the import of non-B3 waste in the same month in 2019, also becomes the urgency of this research. This type of research is descriptive-qualitative research. To analyze the issues raised, this study will use Bryant's concept of environmental politics. There are three points behind the implementation of environmental politics based on Bryant's concept. First is the effect of the environment on the general environment of a country. The second is the existence of interstate relations, and the third is related to the emergence of non-state actors. Through the concept put forward by Bryant, the results of this study indicate that there are at least three urgencies of Indonesia in curbing the import of non-B3 waste in 2019. The first urgency is the emergence of hazardous waste (B3) for the environment and the health of the Indonesian people. Second, an increase in illegal imports of B3 waste in Indonesia. Third, the implementation of the Basel Convention regulations in Indonesia. The results of this study indicate that if the negative impact of the B3 waste content, and also the importance of Indonesia, has become the urgency behind this country's decision to curb the import of non-B3 waste.